Uji Aktivitas Antioksidan Ekstrak Metanol Daun Belimbing Wuluh (Averrhoa bilimbi) - Mustiqawati, Evi; Supardi, Suparman; Juniadin, Juniadin (Jurnal Sains & Kesehatan, 2022)
Belimbing wuluh leaves contain active substances such as flavonoids, saponins, tannins, sulfur, formic acid, peroxidase, calcium oxalate and potassium citrate. Tannins, flavonoids and saponins which have antibacterial activity. Many plants contain antioxidants, one of which is starfruit leaves (Averrhoa bilimbi). Antioxidants are substances that can neutralize free radicals so that atoms with unpaired electrons gain electron pairs. This study aims to determine the antioxidant activity of the methanol extract of star fruit (Averrhoa Blimbi) leaves. The maceration process was carried out on samples of star fruit leaves (Averrhoa Blimbi) and then extracted using methanol as a solvent to analyze the antioxidant activity contained in the leaves of star fruit (Averrhoa Blimbi) using methanol. UV-vis spectrophotometry method. The results of the research that has been carried out on UV-vis spectrophotometry with a wavelength of 517 and has been incubated for 30 minutes shows the IC50 value of the methanol extract of starfruit leaves (Averrhoa Blimbi) of 288.82 mg/mL. The conclusion of this study is the antioxidant properties of methanol extract. Belimbing wuluh leaves contain compounds that act as antioxidants.